Representação escolar: como foi percebida por educandos dos anos iniciais do ensino fundamental de uma escola municipal de São Paulo - Anastácio, Tatiana Guerra (2016)
This research has sought to investigate how the phenomenon of educational representation was understood by students in the early years of elementary school at a municipal school on the outskirts of São Paulo capital. It is a qualitative survey of phenomenological base that has as its main research procedures a participant observation and a reflexive interview. Fourteen meetings have taken place to present the representative development project. After the election in the first year of elementary school has taken place, the elected student answered a reflective interview. The data gathered in those interactions were analyzed according to the methodology of constellations construction and, based on such data, it was possible to register the perception that children, aged from 6 to 10, have on educational representation. Taking into consideration the phenomenological thought and Paulo Freire´s ideas, this research is based on some key concepts, such as: a vision of childhood that values the historical and cultural context where the child is perceived as an integrate human being, able to constitute himself individually and collectively; the act of being representative associated with actions and with actors that are side by side in the process of democratic participation, being the representative or the group leader empowered to act in the name of the represented one; education as an act of political consciousness and based on the relevant part played by human beings in the world, as well as on the need of each person intervene in the surroundings. The search results proved that the educational representation was perceived as a possibility of opening to the world, of being heard, or as a practice provided with a driving force of changes, not only in relation to the individuals, but also to the context where they belong to. It has also become evident, along the search process, the meaning of representation as a building between teachers, on one hand, and students, on the other, as well as between teachers and the management team. However, so that representation can be implemented, it is necessary that all elements of such network are interlinked. Without involving all segments of the school institution in the process, there is the risk of becoming an isolated and empty practice, losing its full meaning in the exercise of democracy